A clinical study of skin disorders in pregnancy - Meena, Manju; Gehlot, Hanslata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Various physiological adaptation of pregnancy related, immunological, metabolic, endocrine and vascular changes occurs during pregnancy which make the pregnant women susceptible to changes of skin and appendages to study the various cutaneous changes of pregnancy. Methods: This study was an observational cross-sectional study conducted in Obstetrics and Gynaecology Department at Umaid Hospital and Skin Department at MDM Hospital, Jodhpur. Total number of 200 pregnant females were included in this study after informed consent and ethical committee clearance in duration of 6 months. Detailed medical and obstetric history of patients were obtained, and physical and dermatological examination were performed. Relevant systemic examination and appropriate investigations were done to confirm diagnosis if required. Results: Most of patients show cutaneous changes, among them physiological changes were most common 196 (98%). The most common physiological change was hyperpigmentation, which was seen in 189 (94.49%) cases followed by striae distensae (76.5%), glandular changes (11.5%) and vascular (9%). Tinea cruris was noted in 04 cases (2%) while scabies was present in 10 females (5%). 15 (7.5%) cases of contact dermatitis were noticed, and psoriasis was found in 3 (1.5%) pregnant females. Herpes genitalis was seen in 1 case (0.5%). The most common Specific dermatoses was pruritic urticarial papules and plaques of pregnancy 10, (5%) followed by pruritic folliculitis 4 (2%), eczema 4 (2%) and intrahepatic cholestsis of pregnancy 2 (1%). Conclusions: Pregnant women are prone to various cutaneous manifestation during pregnancy. A detailed history and awareness of clinical presentation is helpful for confirmation of diagnosis and most appropriate laboratory evaluation is helpful to diminish the maternal and foetal morbidity.